Macrophages protect mycoplasma‐infected chronic myeloid leukemia cells from natural killer cell killing. Issue 2 (13th January 2020) - Choo, Qing Wei Winnie; Koean, Ricky Abdi Gunawan; Chang, Shu‐Chun; Chng, Wee Joo; Chan, Ming Chun; Wang, Wilson; Er, Jun Zhi; Ding, Jeak Ling
Abstract: Macrophages (Mϕ) have been reported to downmodulate the cytotoxicity of natural killer (NK) cell against solid tumor cells. However, the collaborative role between NK cells and Mϕ remains underappreciated, especially in hematological cancers, such as chronic myeloid leukemia (CML). We observed a higher ratio of innate immune cells (Mϕ and NK) to adaptive immune cells (T and B cells) in CML bone marrow aspirates, prompting us to investigate the roles of NK and Mϕ in CML. Using coculture models simulating the tumor inflammatory environment, we observed that Mϕ protects CML from NK attack only when CML was itself mycoplasma‐infected and under chronic infection–inflammation condition. We found that the Mϕ‐protective effect on CML was associated with the maintenance of CD16 level on the NK cell membrane. Although the NK membrane CD16 (mCD16) was actively shed in Mϕ + NK + CML trioculture, the NK mCD16 level was maintained, and this was independent of the modulation of sheddase by tissue inhibitor of metalloproteinase 1 or inhibitory cytokine transforming growth factor beta. Instead, we found that this process of NK mCD16 maintenance was conferred by Mϕ in a contact‐dependent manner. We propose a new perspective on anti‐CML strategy through abrogating Mϕ‐mediated retention of NK surface CD16. Abstract : The collaborative role between natural killer (NK) cells and macrophages (Mϕ) remains unappreciated in hematological tumors. Here, we found that mycoplasma‐infected chronic myeloid leukemia (CML) cells were protected by Mϕ from NK cytotoxicity and this protective effect was associated with Mϕ‐mediated maintenance of NK membrane CD16 level in a contact‐dependent manner. Further studies would shed light into potential therapeutics for CML via modulation of interactions between innate immune cells, NK and Mϕ.